2012
DOI: 10.1080/15427609.2012.705553
|View full text |Cite
|
Sign up to set email alerts
|

Women Vietnam Veterans: Do PTSD Symptoms Mediate Effects of Warzone Service on Health?

Abstract: We assessed the impact of warzone stress on the physical and mental health functioning and well-being of 975 female nurse veterans who had been deployed to Vietnam, and examined whether PTSD symptoms at the time of the survey mediated these relations. A questionnaire was mailed to the Women’s Vietnam Memorial Project members, approximately 25 – 30 years after their wartime service. We examined current physical and mental health functioning in relation to several measures of warzone stress and PTSD symptoms, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Our research team has already reported on associations between poorer physical and mental health outcomes in later life and higher reported warzone stress exhibited by the deployed nurses in this cohort. We found that their PTSD symptoms mediated the effect of warzone stressors on their mental, but not physical, health functioning ( Pless Kaiser, Spiro, Lee and Stellman 2012 ). In another study, we found cumulative trauma exposure (childhood and adulthood trauma, and combat) to be related to poorer mental and physical health functioning, with each type of trauma uniquely contributing to outcomes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our research team has already reported on associations between poorer physical and mental health outcomes in later life and higher reported warzone stress exhibited by the deployed nurses in this cohort. We found that their PTSD symptoms mediated the effect of warzone stressors on their mental, but not physical, health functioning ( Pless Kaiser, Spiro, Lee and Stellman 2012 ). In another study, we found cumulative trauma exposure (childhood and adulthood trauma, and combat) to be related to poorer mental and physical health functioning, with each type of trauma uniquely contributing to outcomes.…”
Section: Introductionmentioning
confidence: 97%
“…2 ). We have previously found length of service to be an important factor related to outcomes ( Pless Kaiser et al, 2012 ). Therefore, throughout these analyses we have stratified the military women by length of service (short-term, middle and long-term career military).…”
Section: Introductionmentioning
confidence: 99%